Provision of first requirements schools, kap and risk perception towards safety and health among School Health Teachers in Kota Bharu, Kelantan - Abdullah, Sarimah (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2010)
Objective: This study was conducted to explore the risk perception towards safety and health among secondary school health teachers . Study design: A cross-sectional study was conducted to gather information on the risk perception towards safety and health in schools among secondary school health teacher . Methods: A structured self administered questionnaires was developed by a group of experts including Public Health Specialist and Emergency Physician. It consists of three domains; risk perception at school, outside school and magnitude and severity of risk at school. Internal consistency reliability using Cronbach's alpha statistics was excellent with the value of0.945, 0.920 and 0.958 respectively. Data was analysed using SPPS version 14 for descriptive statistics and item analysis . Results: One hundred and five secondary school health teachers were recruited in this study. Majority of them were Malays (90%) and females (70%). Mean (SD) age was 41.7 (7.05) years and working experience was 16.24 (7.12) years. The highest risk areas identified in risk perception at school, were injury consequence of fire (58.1 %), explosion (53.3%) and fall of object ( 48.6%). The highest influence to the magnitude and severity of risk in schools was giving a bad consequence to future community (56.2%) followed by news published by newspapers and mass media (51.4%) . Conclusions: The validated questionnaire was reliable and able to assess risk perception towards safety and health among secondary school health teachers. The highest risk areas identified in risk perception at school should be entertained seriously by the school administrative in order to make the school environment condusive, safe and healthy .